Allegorical Prowess of Shata: An Example from the Song A sha Ruwa ba Laifi ba ne - Garba, Salisu (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
The sublime nature of the thought of poets and their expertise make them articulate their experiences in a most peculiar and unique language. This paper titled: Allegorical Prowess of Shata: A Study of the Song ‘A Sha Ruwa Ba Laifi Ba Ne, aimed at examining the Hausa community of 1960s and the issue of some social vices, as skillfully and allegorically portrayed by Shata in the song. In his expertise, Shata allegorically insinuates the weakness of the social Institutions of the Hausa Society of 1960s which aids the deviant behaviour of alcohol consumption and other social vices, citing Kano as an example. The article further aimed at examining the strategies employed by the Artist to portray the menace and dissuade the community from the vice, in the most allegorical elegance. The two versions of the song, with their English renditions used for final analysis were generated from Haussler (1987:136) and Furniss, (1996:153) with some modifications from the author of the paper, while the third Hausa version was generated from Gusau (2008:430). The theory of Ethnomethodology, is adopted as a theoretical framework for the final analysis of the paper, since it was an abnormal behaviours that led to the disruption of so many systems in the Society. The paper thus concludes that, the artist allegorically laments the prevailing social ailment of the then Hausa community, with particular reference to alcohol consumption and other related social vices associated with it, such as adultery and theft. The song serves as a reminder of the social problems bedeviling the society which also inspires the informal and formal social agents to quest for attitudinal change in Kano city and its environs via social control. In addition, the artist alludes to three categories of social effects of alcohol. They include: acts of irrationality, pagan practices and death trap. The study establishes that, the song is a good documentary of the social history of the then Hausa society. It also attests the competency of Shata in his effective use of allegorical technique and his skills in poetic composition.